EXPLOITATION OF VARIABILITY THROUGH MUTAGENESIS IN CHRYSANTHEMUM (CHRYSANTHEMUM MORIFOLIUM RAMAT.) VAR. MAGHI - D. B. KAPADIYA; S. L. CHAWLA; A. I. PATEL; T. R. AHLAWAT (The Bioscan, 2014)
Rooted cuttings of chrysanthemum variety ‘Maghi’ were treated with three concentrations each of EMS and DES (0.02, 0.03 and 0.04 %) and five doses of gamma rays (0.5, 1.0, 1.5, 2.0 and 2.5 kR) to exploit variability and evaluated for heritable effects on various parameters viz. survival rate, morphological and flowering. Reduction in survival rate and various morphological parameters was recorded with chemical mutagens and higher doses of gamma rays. All the mutagenic treatments delayed flowering up to 6 to 7 days whereas flowering duration was significantly reduced. Flower head diameter (3.44 and 3.57 cm), number of ray (130.27 and 132.60) and disc florets (27.93 and 26.33) were significantly increased with 0.5 and 1.0 kR gamma rays, respectively. Flower weight, number of flowers and flower yield per plant were highest at the lowest dose of γ-rays. Total abnormalities in vegetative and floral characters were higher in γ-rays as compared to EMS and DES. Variety ‘Maghi’ exhibited two foliage mutants with 0.03 per cent EMS and 1.0 kR gamma rays, and these mutants lost their flowering ability.